Disasters and Their Effects on Child Development - Muzamil Hussain Al Hussaini; Naseem Kausar; Fitri Indriani (International Journal of Learning Reformation in Elementary Education, 2022)
The special section's papers collectively paint a picture of where disaster and development in children and adolescents research is at. The articles' diversity is impressive; they cover a wide range of crisis circumstances, such as war and the use of child soldiers, terrorism and political unrest, hurricanes and tsunamis, earthquakes and floods, as well as political unrest and climatic change. There are representations of specific calamities that happened in nine different nations. The articles cover a wide range of ages, from very young children through adolescents. In this field of study, longitudinal research and studies that focus on developmental processes are still uncommon. Although a few articles discuss additional levels of analysis, such as biological function and relationships, the majority of the articles concentrate on a behavioral level of function and analysis.